ASTM designation D2358-89 : Standard test method for separation of active ingredient from surfactant and syndet compositions. (West Conshohocken (Pa.) : ASTM International)
1.1 This test method covers the procedure for the separation and purification of active ingredient from surfactants and syndet compositions. The separated active ingredient may be used for qualitative examinations. This test method also permits the estimation of total active ingredient level present in the sample under test. 1.2 This test method yields the active ingredient together with other alcohol-soluble materials and therefore is useful only in estimating the actual active ingredient level. Correction for the amount of the most common contaminant, sodium chloride, is shown by a separate determination.
Keywords: Normen